2018
DOI: 10.1111/ggi.13530
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of clinical presentation on outcomes in older patients with myocardial infarction

Abstract: Aim Myocardial infarction without chest pain misleads the clinician, resulting in a diagnosis delay and an increase of mortality. The main objective of the present study was to determine the risk factors of atypical presentation in older patients with myocardial infarction. Methods All consecutive patients aged ≥75 years presenting with myocardial infarction and hospitalized in the cardiology intensive care unit were included in the present prospective multicenter observational study. All patients benefited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…This work is one in a few studies focusing on risk assessing only in elderly and very elderly patients during AMI. Our study showed a significant association between selected biomarkers and cardiac mortality during the hospital stay, which was similar to other authors' results [19][20][21]. Levels of all biomarkers were higher in non-surviving patients after AMI.…”
Section: Discussionsupporting
confidence: 92%
“…This work is one in a few studies focusing on risk assessing only in elderly and very elderly patients during AMI. Our study showed a significant association between selected biomarkers and cardiac mortality during the hospital stay, which was similar to other authors' results [19][20][21]. Levels of all biomarkers were higher in non-surviving patients after AMI.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the vulnerable and frail populations had more PIMs than the robust group even when the disease burden, as measured by the Charlson comorbidity score, was comparable. Presentation of illness differs between older and younger adults, with older patients showing more atypical signs and symptoms, potentially requiring more medication and therefore having an increased pill burden [21][22][23]. Unusual symptoms might result in more prescriptions and, indeed, probably more PIMs.…”
Section: Discussionmentioning
confidence: 99%
“…The only factors associated with atypical clinical signs in our study were diabetes and infection with S. aureus. Diabetes is a known risk factor for atypical manifestation of myocardial infarction (without chest pain) (34) and asymptomatic bacteriuria. Diabetic patients are also more susceptible to S. aureus colonization (35) and bacteremia (36).…”
Section: Discussionmentioning
confidence: 99%